Natural Area Weeds: A Property Owner's Guide to Melaleuca Control - Kenneth A. Langeland; Stephen F. Enloe; James P. Cuda (EDIS)
This 6-page fact sheet discussing Melaleuca is a minor revision. Written by K. A. Langeland, S. F. Enloe, and J. P. Cuda, and published by the Agronomy Department. Original publication date October 2005. Revised July 2016.